Endodermal/ectodermal interfaces during pharyngeal segmentation in vertebrates. Issue 5 (8th September 2014) - Shone, Victoria; Graham, Anthony
Abstract A key event in the formation of the pharyngeal arches is the outpocketing of the endodermal pharyngeal pouches and the establishment of contact with the overlying ectoderm. However, relatively little is known about how the endoderm and ectoderm relate to each other at these points of contact and the extent to which this differs between the pouches. We have therefore detailed the interactions between the pharyngeal pouches and ectoderm in the chick embryo. Unlike the other pouches, the first pouch does not sustain direct contact with the ectoderm but separates after initial contact. Contrastingly, a perforation is formed between the second pouch and cleft that creates an external opening into the pharynx. Finally, the third and fourth pouch endoderm can be seen to bulge outwards through the ectoderm, although external openings to the pharyngeal lumen are not established. To understand whether these behaviours represent derived or ancestral features, we characterised the pharyngeal ectodermal–endodermal interfaces in the shark embryo. We found that the pouches of the posterior gill‐bearing arches in this species also displayed the outward bulging of the endoderm into the ectoderm, although openings were established. We further used genetic tools to detail unambiguously the relationship between the endoderm and ectoderm in zebrafish and mouse embryos and again found that the posterior pouches break through the ectoderm. Thus different pharyngeal pouches establish different topological relationships with the overlying ectoderm and the posterior pouches initiate the developmental programme for the formation of gills, be they amniotes or anamniotes.